Anchor Borrower Programme on Agricultural Commodity Price and Employment Generation in Kebbi State, Nigeria - Zakaree S., Saheed; A.A., Alexander; Abdulmumin A., Isa; O.A., Adeneye (European Scientific Journal, ESJ, 2018)
Low investment in the agricultural sector, as well as problem of financing are among the major challenges hindering farmers in the rural areas engaging in mechanized farming that might increase food supply, and thereby checking the agricultural commodity prices, and possibly creating more job opportunity in the agricultural sector. In an effort to meet the food supply for the growing population of the country, the government introduced various policies aimed at achieving self-sufficiency in basic food supply, among these policies is the Anchor Borrower Programme. This study examines the impact of Anchor Borrower Program on agricultural commodity price and employment generation in Kebbi state, Nigeria. Data were collected through interview and structured questionnaire administered to a sample of 400 farmers in Argungu L.G.A, of which 360 questionnaire were correctly filled and returned. A multiple regression analysis was used to analyse the data. The results reveal that Anchor Borrower Programmes (ABP) supports for farmer have a positive and statistically significant impact on agricultural commodity price (ACP) and employment generation (EMPG) in agricultural sector in Kebbi state, particularly in Argungu LGA. Based on the findings of this study, it is recommended that anchor borrower programme policy in Nigeria should be encouraged and subjected to periodic review so as to provide more platforms for employment generation and stabilize agricultural commodity price in Kebbi state, particularly in Argungu LGA.